Increased Ankle Plantar Flexor Stiffness Is Associated With Reduced Mechanical Response to Stretch in Adults With CP - Lorentzen, Jakob; Frisk, Rasmus Feld; Nielsen, Jens Bo; Barber, Lee (Frontiers in Bioengineering and Biotechnology, 2021)
Hyperexcitable stretch reflexes are often not present despite of other signs of spasticity in people with brain lesion. Here we looked for evidence that increased resistance of the plantarflexor muscle-tendon unit may contribute to a reduction in the stretch reflex response in adults with cerebral palsy (CP). 17 neurologically intact (NI) adults (mean age 36.1; 12 female) and 13 adults with CP (mean age 33.1; 5 female) participated in the study. Subjects were seated in an armchair with the examined foot attached to a foot plate, which could be moved by a computer-controlled electromotor. An ultrasound probe was placed over the medial aspect of the leg to measure the length of medial gastrocnemius muscle fascicles. Slow (7 deg/s) and fast (200 deg/s) stretches of the plantarflexors were applied throughout the range of movement (ROM) of the ankle joint at 10 deg intervals. It was checked by EMG electrodes that the slow stretches were sufficiently slow not to elicit any stretch reflex activity, whereas the fast stretches were sufficiently quick to elicit a maximal stretch reflex. The torque elicited by the stretches was measured together with changes in the length of medial gastrocnemius muscle fascicles. Muscle fascicles increased significantly in length with increasing dorsiflexion position in both populations (p<0.001), but the fascicles were shorter in the CP population at all positions. Slow stretches elicited significantly larger torque and significantly smaller length change of muscle fascicles at ankle joint positions of 90 deg and below in CP than in NI (p<0.001). Fast stretches elicited larger torque responses at ankle joint positions of 80-100 deg in the NI than in the CP group (p<0.01). A significant negative correlation was observed between the torque response and muscle fascicle length change to slow stretch and the torque response to fast stretch in CP (p<0.05), but not in NI. These findings support that increased passive resistance of the ankle plantarflexor muscle-tendon unit and development of contractures may conceal stretch reflex hyperexcitability in adults with CP. We argue that this should be taken into account in the neurological examination of spasticity.